The cytosolic N-terminal region of heterologously-expressed transmembrane channel-like protein 1 (TMC1) can be cleaved in HEK293 cells. - Soichiro Yamaguchi; Maho Kamino; Maho Hamamura; Ken-Ichi Otsuguro (PLoS ONE, 2023)
Transmembrane channel-like protein 1 (TMC1) is a transmembrane protein forming mechano-electrical transduction (MET) channel, which transduces mechanical stimuli into electrical signals at the top of stereocilia of hair cells in the inner ear. As an unexpected phenomenon, we found that the cytosolic N-terminal (Nt) region of heterologously-expressed mouse TMC1 (mTMC1) was localized in nuclei of a small population of the transfected HEK293 cells. This raised the possibility that the Nt region of heterologously-expressed mTMC1 was cleaved and transported into the nucleus. To confirm the cleavage, we performed western blot analyses. The results revealed that at least a fragment of the Nt region was produced from heterologously-expressed mTMC1. Site-directed mutagenesis experiments identified amino acid residues which were required to produce the fragment. The accumulation of the heterologously-expressed Nt fragment into the nuclei depended on nuclear localization signals within the Nt region. Furthermore, a structural comparison showed a similarity between the Nt region of mTMC1 and basic region leucine zipper (bZIP) transcription factors. However, transcriptome analyses using a next-generation sequencer showed that the heterologously-expression of the Nt fragment of mTMC1 hardly altered expression levels of genes. Although it is still unknown what is the precise mechanism and the physiological significance of this cleavage, these results showed that the cytosolic Nt region of heterologously-expressed mTMC1 could be cleaved in HEK293 cells. Therefore, it should be taken into account that the cleavage of Nt region might influence the functional analysis of TMC1 by the heterologous-expression system using HEK293 cells.